2014
DOI: 10.1099/mic.0.073353-0
|View full text |Cite
|
Sign up to set email alerts
|

A small heat-shock protein (Hsp20) regulated by RpoS is essential for cyst desiccation resistance in Azotobacter vinelandii

Abstract: In Azotobacter vinelandii, a cyst-forming bacterium, the alternative sigma factor RpoS is essential to the formation of cysts resistant to desiccation and to synthesis of the cyst-specific lipids, alkylresorcinols. In this study, we carried out a proteome analysis of vegetative cells and cysts of A. vinelandii strain AEIV and its rpoS mutant derivative AErpoS. This analysis allowed us to identify a small heat-shock protein, Hsp20, as one of the most abundant proteins of cysts regulated by RpoS. Inactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 45 publications
(70 reference statements)
0
31
0
Order By: Relevance
“…PCC6803 (Hsp16.6), Xanthomonas campestris (HspA) and the cyst forming bacterium Azotobacter vinelandii (Hsp20). Notably, in these bacteria Hsp16.6 and HspA are essential for thermotolerance [96, 121], and Hsp20 is essential for cyst desiccation resistance [122]. In other bacteria, such as E. coli , there are two sHsps, one of which (IbpA in E. coli ) has low chaperone activity alone, but which acts to enhance chaperone activity of the second sHsp (IbpB in E. coli ) when they form a hetero-oligomer (Fig.…”
Section: Regulation Of Shsp Activitymentioning
confidence: 99%
“…PCC6803 (Hsp16.6), Xanthomonas campestris (HspA) and the cyst forming bacterium Azotobacter vinelandii (Hsp20). Notably, in these bacteria Hsp16.6 and HspA are essential for thermotolerance [96, 121], and Hsp20 is essential for cyst desiccation resistance [122]. In other bacteria, such as E. coli , there are two sHsps, one of which (IbpA in E. coli ) has low chaperone activity alone, but which acts to enhance chaperone activity of the second sHsp (IbpB in E. coli ) when they form a hetero-oligomer (Fig.…”
Section: Regulation Of Shsp Activitymentioning
confidence: 99%
“…A and preliminary data not shown). sHsps of the sHsp20 family are holding chaperones involved in preventing protein aggregation under heat shock, oxidative stress and desiccation in bacteria (Thomas and Baneyx, ; Bojer et al ., ; Kuczynska‐Wisnik et al ., ; Cocotl‐Yanez et al ., ). Despite ubiquitous occurrence, few physiological functions have been assigned to sHsps in prokaryotes.…”
Section: Discussionmentioning
confidence: 97%
“…The shsp20c ‐encoding operon might be regulated by σ S , an alternative sigma factor in stationary phases in response to general stress or nutrient starvation (Battesti et al ., ). Recently, σ S ‐dependent sHsp20 has been reported in Azotobacter vinelandii to be involved in desiccation resistance (Cocotl‐Yanez et al ., ). The distinct production pattern of sHsp20c thus points to a protein quality control function in stationary phase clearly distinct from the sHsp20 core genome protein IbpA.…”
Section: Discussionmentioning
confidence: 97%
“…sHSPs were often found to be highly overexpressed at heat stress-conferring thermotolerance to some organisms (Loomis and Wheeler 1982;Berger and Woodward 1983)but showing no feasible phenotype when disrupted in others (Susek and Lindquist 1989;Praekelt and Meacock 1990). It took detailed biochemical studies to demonstrate that sHSPs act as molecular chaperones both in animals (Jakob et al 1993;Wang and Spector 1995), plants (Lee et al 1995) and bacteria (Chang et al 1996;Thomas and Baneyx 1998).…”
Section: From Discovery To Common Featuresmentioning
confidence: 99%
“…In 1996, after multiple evidence appeared of eukaryotic sHSPs being molecular chaperones (Jakob et al 1993;Boyle and Takemoto 1994;Singh et al 1995;Wang and Spector 1995;Raman et al 1995), Hsp16.3 from Mycobacterium tuberculosis was shown to suppress citrate synthase (CS) thermal aggregation, although it could not protect CS activity nor refold it afterwards (Chang et al 1996). The same year Escherichia coli IbpA & IbpB, previously described as inclusion body associated proteins (Allen et al 1992), were found to co-localize with the aggregated protein fraction in heat shock conditions (Laskowska et al 1996).…”
Section: Chaperone Activity: Stable Interactionsmentioning
confidence: 99%